PELATIHAN AKUNTANSI UNTUK PENYELENGGARAAN PEMBUKUAN SEDERHANA BAGI KUBE JAYA ABADI DESA PENGUDANG - Sarazwati, Raja Yulianita; Mu’azamsyah, Muhammad; Ellmanda, Devis; Kamelda, Kamelda; Carolina, Meidi; Nisyamuddin, Nisyamuddin; Juwita, Rahma Dini; Waskitho, Thessalonica Mutiara (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Simple bookkeeping is a documentation process carried out by employers in a structured manner by collecting data and information related to the company's financial reports. Usually, this simple bookkeeping consists of all financial reports in a company. Financial documentation that is recorded is usually related to assets, expenses, capital, income , budget, prices with output results in the form of presentation of financial reports. The purpose of bookkeeping activities in a business is to reduce or minimize the risk of losing products, assets, and even money belonging to the company. The problem we encountered in Pengudang Village, more precisely at KUBE Jaya Abadi is these business actors do not yet know the importance of a bookkeeping. As a result, they do not know how much their income and expenses are while their business is running. For this reason, we held an "Accounting Training for Simple Bookkeeping for KUBE Jaya Abadi Pengudang Village" which we aimed at business people, especially members of KUBE Jaya Abadi. The method we used during our research was observation and outreach. The results of the survey that we have conducted, the bookkeeping at KUBE Jaya Abadi is still not effective so we have made the bookkeeping into 3 books, namely the production record book, income book, and financial report book. With this activity, it is hoped that it can help improve the performance of business finances carried out and make it easier for business actors to prepare financial reports that are made